Síntese e caracterização de suportes de alumina para aplicação em membranas cerâmicas para processos de separação gasosa - Priscila Cristh Fonseca Alves (2021)
Green technologies are necessary for driving a sustainable production model in order to mitigate the damages caused by the global warming. It has encouraged an energy transition focused on the consumption of low carbon fuels, such as natural gas. The natural gas is found in the form of a mixture of components and it shall be purified to remove contaminants such as carbon dioxide. An alternative to conventional techniques of purification is the use of the inorganic membranes, due to its numerous advantages. The inorganic membranes are composed of several layers and require the use of a substrate to provide structural support. It was developed ceramic supports for the application of membranes to separate CO2 from the natural gas. The inorganic starting powder used was α-alumina with purity above 99 %, bimodal distribution of the particles diameters and average particle size around 3.71 μm. The uniaxial pressing was the forming method used, giving rise to flat ceramic bodies with cylindrical geometry. The influence of two operational parameters in the final substrate properties was investigated. One of them was the addition of the titania sintering agent in the rutile phase and average particle diameter of around 0.56 μm. The concentrations used were 0.5 wt.%, 1 wt.%, 3 wt.% and 5 wt.% of TiO2. The second parameter was the heat treatment temperature and the studied values were: 1300 °C, 1400 °C, 1500 °C and 1600 °C. It was observed that the TiO2 additions of 0.5 wt.% and 1 wt.% in the alumina supports were sufficient to reinforce the ceramic structure by the increasing in the fracture resistance. Subsequent additions of TiO2 (3 wt.% and 5 wt.%) did not influence the porosity values and can reduce the compressive strength. The increase in the sintering temperature enhances the diffusion of ions and the pores closing. The better results of porosity and mechanical strength can be attributed to the alumina supports sintered at 1400 °C and 1500 °C and the doped ones with 0.5 wt.% and 1 wt% of TiO2 and heat treated at 1400 °C. The samples showed pores in the range of 0.049 μm and 3.7 μm, which classifies them as macroporous. The analysis of the gas permeability data proves that the pore network present in the supports is an accessible path for gas permeation, validating the objective of this study, which consists in the obtaining porous substrates suitable for application of membranes in separation processes. The supports developed in this study are suitable for application in microfiltration and ultrafiltration processes. For the nanofiltration and gas separation processes is necessary to deposit successive layers over the support to gradually diminish the pore diameter.